Extraskeletal osteosarcoma: An uncommon variant with rare metastatic sites detected with FDG PET/CT - Ameya D. Puranik; Nilendu C. Purandare; Munita M. Bal; Sneha Shah; Archi Agrawal; Venkatesh Rangarajan (Indian Journal of Medical and Paediatric Oncology)
Extraskeletal osteosarcoma (ESOS) is a rare malignancy, which commonly presents with metastatic disease. Like their osteogenic counterparts, these tumors commonly metastasize to lungs and bones. We report the fluoro-deoxyglucose positron emission tomography findings in a case of ESOS presenting with a combination of rare metastatic sites such as brain, kidney and the bone marrow.